Um estudo comparativo entre Brasil e Chile sobre educação matemática e sua influência nos currículos de matemática desses países - Cerqueira, Dermeval Santos (2012)
This qualitative research at the doctoral level, is within the context of comparative studies on organization and curriculum development in the field of mathematics education, in Brazil and Chile. The purpose of this study is to investigate evidence on the impact of the results of research in mathematics education in the official documents of these countries, drawn from 90s of XX century. The documentary analysis shows that these countries have suffered influences of research findings in the area of mathematics education, including in official documents orientations favoring problem solving, contextualization, the didactic value of history of mathematics, concepts of teaching mathematics, constructivism, the use of technology, especially the use of calculator. Field research allows us to understand the views of different education professionals on the design and development of curricula prescribed, points to the difficulties in achieving the curriculum practiced in public education systems, weave recommendations that must be included in the teacher's work and highlights challenges to implementing the prescribed curriculum